Раціональний підхід до визначення стратегічних пріоритетів підприємства - Отенко, В.І. (Культура народов Причерноморья, 2013)
У статті описано основні принципи раціонального підходу до стратегічного управління
підприємством, зазначені переваги та недоліку раціональної моделі. Описано методологію ситуаційного
управління, в контексті якої виділено основні типи стратегій вирішення управлінських ситуацій:
корпоративну, ділову, функціональну та оперативну. Обґрунтовано першочергове значення
конкурентних стратегій для досягнення стратегічного успіху та реалізації стратегічних пріоритетів
підприємства, та визначено основні елементи, що необхідно враховувати при розробці системи
стратегічного управління ним. В статье описаны основные принципы рационального подхода к стратегическому
управлению предприятием, обозначены преимущества и недостатки рациональной модели. Описана
методология ситуационного управления, в контексте которой выделены типы стратегий решения
управленческих ситуаций: корпоративную, деловую, функциональную и оперативную. Обосновано
первоочередное значение конкурентных стратегий для достижения стратегического успеха и
реализации стратегических приоритетов предприятия, а также определены основные элементы,
которые необходимо учитывать при разработке системы стратегического управления им. The article considers the basic principles of rational approach to strategic management of an
enterprise, the advantages and disadvantages of the rational model are presented. The methodology of
situational management is developed with defining the main types of strategies for solving managerial
situations: corporate , business , functional and operational. Paramount importance of competitive strategies for
achieving strategic success and implementation of the strategic priorities of the enterprise is justified, and the
key elements that are necessary to consider while developing the systems of strategic management are identified.
The factors proposed to consider the set of parameters in production and sales, production and technological
capabilities, financial and economic situation of the company, the state of the market environment , including the
characteristics of suppliers, customers and competitors. It is necessary to carry out ranking all factors to take
account of their importance in the model. The directions of strategic management is the management criteria
and all sorts of constraints on resources ( raw materials , production , time , finance and so on). Develop and
implement strategies for the formation and development of competitive advantage competitive strategies include
the integration of functional and ensure their subordination to corporate development strategy .
Methodology rationalizing strategic choice is to form a complete set of information about strategic options,
knowledge of performance and market technology management ment. Formalizing strategic options involves the
development of competitive strategies classifier, a set of institutional arrangements for strategic choice and
strategy implementation, the formation of optimization models, the definition of criteria and constraints.